Mapping Gene Expression in Excitatory Neurons during Hippocampal Late-Phase Long-Term Potentiation - Chen, Patrick B.; Kawaguchi, Riki; Blum, Charles; Achiro, Jennifer M.; Coppola, Giovanni; O'Dell, Thomas J.; Martin, Kelsey C. (Frontiers in Molecular Neuroscience, 2017)
The persistence of long-lasting changes in synaptic connectivity that underlie long-term memory require new RNA and protein synthesis. To elucidate the temporal pattern of gene expression that gives rise to long-lasting neuronal plasticity, we analyzed differentially-expressed (DE) RNAs in mouse hippocampal slices following induction of late phase long-term potentiation (L-LTP) specifically within pyramidal excitatory neurons using Translating Ribosome Affinity Purification RNA sequencing (TRAP-seq). We detected time-dependent changes in up- and down-regulated ribosome-associated mRNAs over two hours following L-LTP induction, with minimal overlap of DE transcripts between time points. TRAP-seq revealed greater numbers of DE transcripts and magnitudes of LTP-induced changes than RNA-seq of all cell types in the hippocampus. Neuron-enriched transcripts had greater changes at the ribosome-loading level than the total RNA level, while RNA-seq identified many non-neuronal DE mRNAs. Our results highlight the importance of considering both time course and cell-type specificity in activity-dependent gene expression during memory formation.